Programming ArcGIS 10.1 with Python Cookbook - Pimpler Eric (Packt Publishing, 2013)
This book is written in a helpful, practical style with numerous hands-on recipes and chapters to help you save time and effort by using Python to power ArcGIS to create shortcuts, scripts, tools, and customizations. This book is written for GIS professionals who wish to revolutionize their ArcGIS workflow with Python. Basic Python or programming knowledge is essential.